Bad Debts and Depreciation of Fixed Assets on Net Profit of PT. Indofood Sukses Makmur Tbk - M. Rifani Adha; Rininda, Bella Puspita; Yuli Fitriyani; M. Riduan Abdillah; Mufrida Zein (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This research aims to determine the effect of bad debts and depreciation of fixed assets on net profit. This research uses quantitative research which uses 20 samples of PT's quarter 1, quarter 2, quarter 3 and quarter 3 PT. Indofood Sukses Makmur Tbk. The research results show that bad debts have no effect on net profit, while depreciation of fixed assets has a significant effect on net profit. If simultaneously, bad debts and depreciation of fixed assets have a positive and significant effect on net profit interest.